2022
DOI: 10.1021/acs.est.2c05684
|View full text |Cite
|
Sign up to set email alerts
|

Green Tides Significantly Alter the Molecular Composition and Properties of Coastal DOC and Perform Dissolved Carbon Sequestration

Abstract: Despite green tides (or macroalgal blooms) having multiple negative effects, it is thought that they have a positive effect on carbon sequestration, although this aspect is rarely studied. Here, during the world’s largest green tide (caused by Ulva prolifera) in the Yellow Sea, the concentration of dissolved organic carbon (DOC) increased by 20–37% in intensive macroalgal areas, and thousands of new molecular formulas rich in CHNO and CHOS were introduced. The DOC molecular species derived from U. prolifera co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…The photosynthetic growth of massive U. prolifera during the early stage of green tides removes substantial DIC from seawater to convert it into algal biomass. , Large amounts of DOC are concurrently released from growing macroalgae, which leads to a significant increase in DOC concentrations. , However, when the green tide enters the decline stage (i.e., late-bloom stage), the photosynthetic growth of macroalgae is significantly weakened or even ceases, and the microbial remineralization of macroalgae-derived organic carbon and macroalgal respiration release a large amount of DIC, which exceeds the absorption capacity of macroalgae, resulting in an increase in the seawater DIC concentration. ,, Therefore, the massive macroalgae at the late-bloom stage has a significant impact not only on the coastal organic carbon pool but also on the inorganic carbon pool. Several recent studies have observed an evident increase in the mean concentrations of DIC and TAlk in certain regions of the South Yellow Sea during the late-bloom period of green tides. , In fact, although the distribution area of U.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The photosynthetic growth of massive U. prolifera during the early stage of green tides removes substantial DIC from seawater to convert it into algal biomass. , Large amounts of DOC are concurrently released from growing macroalgae, which leads to a significant increase in DOC concentrations. , However, when the green tide enters the decline stage (i.e., late-bloom stage), the photosynthetic growth of macroalgae is significantly weakened or even ceases, and the microbial remineralization of macroalgae-derived organic carbon and macroalgal respiration release a large amount of DIC, which exceeds the absorption capacity of macroalgae, resulting in an increase in the seawater DIC concentration. ,, Therefore, the massive macroalgae at the late-bloom stage has a significant impact not only on the coastal organic carbon pool but also on the inorganic carbon pool. Several recent studies have observed an evident increase in the mean concentrations of DIC and TAlk in certain regions of the South Yellow Sea during the late-bloom period of green tides. , In fact, although the distribution area of U.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Large amounts of DOC are concurrently released from growing macroalgae, which leads to a significant increase in DOC concentrations. 5,10 However, when the green tide enters the decline stage (i.e., late-bloom stage), the photosynthetic growth of macroalgae is significantly weakened or even ceases, and the microbial remineralization of macroalgae-derived organic carbon and macroalgal respiration release a large amount of DIC, which exceeds the absorption capacity of macroalgae, resulting in an increase in the seawater DIC concentration. 2,14,15 Therefore, the massive macroalgae at the late-bloom stage has a significant impact not only on the coastal organic carbon pool but also on the inorganic carbon pool.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cell structure of pre-decomposed U. prolifera has been destroyed during the pretreatment process, and once it was thrown into water, almost all organic matter was released rapidly. Different concentrations and compositions of organic matter also affected microbial community succession (Liang et al, 2021;Li et al, 2022a), leading to different trends in FDOM components.…”
Section: Changes In the Bioactivity Of Organic Mattermentioning
confidence: 99%
“…The dynamic changes in DOM composition was the driving force for the bacterial community (Liang et al, 2021;Li et al, 2022a). Proteobacteria, which widely existed in the environment, were always in relative high abundance in the degradation process of fresh and the pre-decomposed U. prolifera.…”
Section: Distinctive Impacts On Microbial Community Structurementioning
confidence: 99%